Anarchist Immigrants in Spain and Argentina - Baer, James A. (Book collections on Project MUSE., 2015)
From 1868 through 1939, anarchists' migrations from Spain to Argentina and back again created a transnational ideology and influenced the movement's growth in each country. James A. Baer follows the lives, careers, and travels of Diego Abad de Santillán, Manuel Villar, and other migrating anarchists to highlight the ideological and interpersonal relationships that defined a vital era in anarchist history. Drawing on extensive interviews with Abad de Santillán, Jose Grunfeld, and Jacobo Maguid, along withunusual access to anarchist records and networks, Baer uncovers the ways anarchist migrants in pursuit of jobs and political goals formed a critical nucleus of militants, binding the two countries in an ideological relationship that profoundly affected the history of both. He also considers the impact of reverse migration and discusses political decisions that had a hitherto unknown influence on the course of the Spanish Civil War. Personal in perspective and transnational in scope, Anarchist Immigrants in Spain and Argentina offers an enlightening history of a movement and an era.